Interhemispheric Transcingulate Sulcus Approach to Deep-Seated Medial Frontal and Parietal Lesions—Fiber Dissection Study With Illustrative Cases. Issue 3 (20th March 2023) - Gungor, Abuzer; Gurses, Muhammet Enes; Dogan, Eray; Varol, Eyup; Gökalp, Elif; Etli, Mustafa Umut; Ozoner, Baris
Abstract : BACKGROUND: Surgery for lesions located in the medial frontal and parietal lobes can be quite challenging for neurosurgeons because of morbidities that may arise from damage to critical midline structures or intact neural tissue that need to be crossed to reach the lesion. In our anatomic studies, the cingulate sulcus was observed as an alternative access route for lesions located in medial frontal and parietal lobes. OBJECTIVE: To explain the microsurgical anatomy of the medial hemisphere and cingulate sulcus and to demonstrate the interhemispheric transcingulate sulcus approach (ITCSA) with 3 clinical cases. METHODS: Five formalin-fixed brain specimens, which were frozen at −18 °C for at least 2 weeks and then thawed under tap water, were gradually dissected from medial to lateral. Diffusion fiber tracking performed using DSI Studio software in data was provided by the Human Connectome Project. Clinical data of 3 patients who underwent ITCSA were reviewed. RESULTS: Cingulate sulcus is an effortlessly identifiable continuous sulcus on the medial surface of the brain. Our anatomic dissection study revealed that the lesions located in the deep medial frontal and parietal lobes can be reached through the cingulate sulcus with minor injury only to the cingulum and callosal fibers. Three patients were treated with ITCSA without any neurological morbidity. CONCLUSION: Deep-seated lesions in the medial frontal lobe and parietal lobe medial to the corona radiata can be approached by using microsurgical techniques based on anatomic information. ITCSA offers an alternative route to these lesions besides the known lateral transcortical/transsulcal and interhemispheric transcingulate gyrus approaches.